Foundation: Foundation and Empire; Second Foundation - Asimov, Isaac 1920-1992; Dirda, Michael (New York, NY Everyman's Library, 2010)
The Foundation, established after the Old Empire gives way to barbarism, fights against a mutant strain called the Mule and tries to get rid of the Second Foundation after learning it will inherit a future Empire.
Foundation -- Foundation and empire -- Second foundation.
"This is a Borzoi book."
Includes bibliographical references (p. xxii-xxiv), and chronology.
Keywords: 20th Century (1901-2000); Literature